The Main Statements of the Consensus “Maastricht-VI” (2022) on the Diagnostics and Treatment of Helicobacter pylori Infection - A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to present an analysis of the published materials of the consensus “Maastricht-VI” on the management of patients with Helicobacter pylori (H. рylori) infection.Key points. The content of the new consensus “Maastricht-VI” largely corresponds to that of the previous “Maastricht-V” consensus. This refers to the methods of diagnostics of this infection, indications for eradication. The introduction of eradication schemes of the 3rd and 4th lines, as well as a double scheme with increased doses of proton pump inhibitors (PPI) and amoxicillin can be considered new. The important role of measures that increase the effectiveness of eradication (14-day duration of the course, increasing the dose of PPI, the use of probiotics) is emphasized.Conclusion. The publication of materials of the new consensus “Maastricht-VI” will contribute to improving the results of H. рylori eradication therapy.